A Sequential Entry Model with Strategic Use of Excess Capacity - Brad Barham; Roger Ware (Queen's University, Department of Economics, 1991)
A model of sequential entry with Leontief costs is studied in which demand is iso-elastic. Some or all firms may hold excess capacity in the perfect equilibrium to the entry game. Firms with a first mover advantage trade off the positioning value of a large investment in capacity, leading to a large market share, against the possible costs of bearing the burden of entry deterrence through holding excess capacity in equilibrium.
Keywords: 330